A Novel Nonlinear Control of Boost Converter using CCM Phase Plane - Eko Setiawan; Ichijo Hodaka (Institute of Advanced Engineering and Science, 2018)
Boost converter is one of fundamental DC-DC converters and used to deliver electric power with boosted voltage in many electrical systems. Several control strategies have been applied to control a boost converter delivering a constant output voltage. Generally, boost converter works in two modes; one is called a Continuous Conduction Mode (CCM). Many researches use CCM model in the controller design, but they never ensure that the controller always works in CCM. This paper proposes novel nonlinear controller of boost converter designed using the modiﬁcation of ﬂow in phase plane. The proposed controller guarantees that the boost converter works only in CCM region. The simulation result conﬁrms that our proposed controller brings the state variables from any initial point to a desired operating point successfully.